Permanent education in health. An instrument to enhance interpersonal relations in nursing work - Rocha, Laurelize; Ribeiro, Juliane (Investigación y Educación en Enfermería, 2025)
This is a reflexive study about the need to adopt Permanent Education in Health, as an instrument capable of transforming interpersonal relations in nursing work, as it values and respect collective construction with a view to the qualification of care. Privileging specialization programs only, with a focus on work techniques, on educative processes, as a training strategy for health services, ends up reinforcing the fragmentation of care, teams and the work process. In conclusion, Permanent Education in Health serves not only as teaching and learning practice to update and transform practices, but also influences team relations, transforming joint action processes and, at the same time, implying each subject-worker involved in health practices.